2019
DOI: 10.1080/20002297.2019.1676486
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between genetic defects in the complement cascade andPorphyromonas gingivalisin Alzheimer’s disease?

Abstract: Defects, as determined by Genome-Wide Association Studies (GWAS), in the complement cascade of innate immunity have been suggested to play a key role in Alzheimer's disease (AD). These defective genes encode sub-component 1s (C1s), complement receptor 1, complement component 9, and clusterin, a fluid-phase regulatory protein. A dysregulated complement cascade has been shown to relate to cell activation, defective complement mediated clearance and possible cognitive decline in AD patients. Porphyromonas gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 110 publications
(174 reference statements)
2
32
0
Order By: Relevance
“…It has been reported that SNPs rs3818361 and rs6656401 of the CR1 gene are associated with increased likelihood of AD [49]. This supports a CR1 gene defect in AD [5]. CR1 helps with regulating the complement cascade and promotes phagocytosis of cellular debris and Aβ plaques, and adherence of immune complexes to erythrocytes [5].…”
Section: Cr1 Genementioning
confidence: 85%
“…It has been reported that SNPs rs3818361 and rs6656401 of the CR1 gene are associated with increased likelihood of AD [49]. This supports a CR1 gene defect in AD [5]. CR1 helps with regulating the complement cascade and promotes phagocytosis of cellular debris and Aβ plaques, and adherence of immune complexes to erythrocytes [5].…”
Section: Cr1 Genementioning
confidence: 85%
“…A nationwide, retrospective, matched-cohort study in Taiwan showed that patients with chronic periodontitis and gingivitis have a higher risk of developing dementia compared to those with healthy gums (Tzeng et al, 2016). Moreover, recent accumulating evidence has demonstrated a causal relationship between oral microbiome and AD (Paganini-Hill et al, 2012;Harding et al, 2017;Liu et al, 2019b;Panza et al, 2019;Olsen and Singhrao, 2020). For example, P. gingivalis, the most common periodontal bacteria causing periodontal disease, was capable of inducing accumulation of amyloidbeta plaques and neurofibrillary tangles following experimental oral infection in mice (Dominy et al, 2019).…”
Section: Oral Microbiome and Alzheimer's Diseasementioning
confidence: 99%
“…As mentioned, proteolysis is important for this bacterium to obtain nutrition through breakdown of proteins. Gingipains are also important for degradation of antibacterial peptides [27] and for the bacterium to evade the complement system [28,29].…”
Section: Porphyromonas Gingivalis and Parkinson's Diseasementioning
confidence: 99%